Oral health, the perspective of the inmate and the context of vulnerability - Fadel, Cristina Berger; Valentim, Lígia Maria; Fillus, Thaís Marília; Langoski, Jean Érick; Bordin, Danielle (Universidade Estadual Paulista Júlio de Mesquita Filho, 2015)
AbstractIntroductionThe increase in prison populations is a phenomenon which is systematically rising throughout the world, leading to overcrowding of prisons, which has direct consequences on the health conditions of the individuals.ObjectiveTo explore the relationship among oral health, the life path and the perception of subjects in a vulnerability context.Material and methodThis is a qualitative study, developed with inmates in a State Penitentiary. To obtain and process the data, individual interviews and the Thematic Content Analysis technique were used.ResultThe interviewees showed limited perception of the process of oral health and disease fostered by the experiences of relatives and by knowledge acquired in the street or from the media. The life path in prison seemed to have little influence on this understanding. However, the prison experience influenced the oral condition of the inmates by facilitating access to dental service, oral hygiene materials and the improvement in their health knowledge and habits. The oral health results presented were, generally, in agreement with so-called common sense and with studies developed in socially similar populations.ConclusionThus, considering the limitations imposed by the way data were collected, in prison and in a vulnerability context; a non-harmful influence on the condition studied regarding the oral health of inmates is suggested.

ResumoIntroduçãoO aumento da população encarcerada é um fenômeno que vem sistematicamente sofrendo incremento no mundo todo, levando a superlotação dos presídios, a qual tem consequência direta nas condições de saúde destes indivíduos.ObjetivoExplorar a relação entre saúde bucal, trajetória de vida e percepção de sujeitos em contexto de vulnerabilidade.Material e métodoTrata-se de um estudo qualitativo desenvolvido junto a encarcerados de uma Penitenciária Estadual. Para obtenção e tratamento dos dados utilizou-se entrevista individual e técnica da Análise de Conteúdo Temática.ResultadoOs entrevistados apresentaram uma percepção limitada do processo saúde e doença bucal, fomentada por experiências de familiares e de conhecimento adquirido na rua ou na mídia. A trajetória de vida em cárcere pareceu pouco influenciar neste entendimento. No entanto, a vivência no cárcere influenciou na condição bucal dos encarcerados através da facilitação do acesso ao serviço odontológico e a materiais de higiene bucal e melhoria em seus conhecimentos e hábitos de saúde. As referências de saúde bucal expostas mostraram-se, em geral, consonantes com o chamado senso comum e com estudos desenvolvidos em populações socialmente similares.ConclusãoDesta forma, considerando-se as limitações impostas pela forma da coleta dados, sob um contexto de cárcere e vulnerabilidade, sugere-se uma influência não prejudicial da condição estudada sobre a saúde bucal dos encarcerados.
Saúde bucal, a ótica do encarcerado e o contexto da vulnerabilidade
Keywords: Social vulnerability; oral health; life style; Vulnerabilidade social; saúde bucal; estilo de vida